New Insights into Molecular Mechanisms Underlying Neurodegenerative Disorders - Villa, Chiara; Paudel, Yam Nath; Piperi, Christina (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Neurodegenerative disorders encompass a broad range of sporadic and/or familial debilitating conditions characterized by the progressive dysfunction and loss of selective neuronal populations, determining different clinical phenotypes. Emerging research data indicate an interplay of genetic factors and epigenetic mechanisms underlying neurodegenerative processes, which lead to increased prevalence of neurodegenerative disorders. In concert with the constant increase in the aging population, neurodegenerative disorders currently represent a major challenge to public health worldwide. Despite recent advances in clinical and preclinical research, the pathogenesis of these disorders still remains poorly understood, without effective treatments being available to halt the neurodegenerative processes, but rather aiming at relieving symptoms. Therefore, a critical evaluation of current research data and in-depth understanding of the molecular mechanisms that lead to neurodegeneration are crucial in order to identify potential therapeutic targets that can pave the way to the development of novel and promising therapies. This Special Issue is focused on novel molecular data in the field of neurodegeneration that associate with the onset and progression of neurodegenerative diseases. We are particularly interested in original articles and reviews that provide new insights into the main molecular pathogenic mechanisms underlying neurodegenerative disorders, aiming to identify potential biomarkers and novel therapeutic strategies.